PARAUNITARY FILTER BANKS BASED ON THE QUATERNIONIC ALGEBRA SYNTHESIS FOR COMPUTING STRUCTURES WITH FIXED point arithmetic - E. V. Rybenkov; N. A. Petrovsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The synthesis method of paraunitary filter banks based on the quaternion algebra (Q-PUBF) for computing structures constrained by fixed point arithmetic is proposed. Synthesis problem using method of Lagrange multipliers is solved. It is shown that the Q-PUBF represents integer transform and can be used for image coding by scheme L2L (lossless-to-lossy).